2014
DOI: 10.7895/ijadr.v3i1.119
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of the effectiveness of a professional development program on the academic achievement and classroom behavior of students with Fetal Alcohol Spectrum Disorder in British Columbia, Canada

Abstract: Aim: Exploratory assessment of a professional development program for teachers supporting students with Fetal Alcohol Spectrum Disorder (FASD).Design: A mixed-method research design, using qualitative descriptive and quasi-experimental methods, was employed. Setting:The study occurred in selected public elementary schools in a British Columbia school district. Participants:Elementary school teachers and students with FASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Our review identified 16 school/education-based management interventions [83,84,85,86,87,88,89,90,91,92,93,96,97,98]. Two of the above-mentioned management interventions aimed at improving mathematical skills and behavior in children with FASD [83,87].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review identified 16 school/education-based management interventions [83,84,85,86,87,88,89,90,91,92,93,96,97,98]. Two of the above-mentioned management interventions aimed at improving mathematical skills and behavior in children with FASD [83,87].…”
Section: Resultsmentioning
confidence: 99%
“…The pieces of training were effective in improving cognitive performance [84] increasing postural sway velocity [89] in children with FASD and improving the digit span in children [97]. Additionally, we also found a program effective for the professional development of teachers [98].…”
Section: Resultsmentioning
confidence: 99%
“…The FASD literature does address helping children cope with change. Within the school system teachers have had to help children with FASD cope with changes to their medications and home environment (e.g., change in the caregiver ;Clark et al, 2014). The current study suggests that while helping the child accept change can be challenging at first, with patience and various skills the child can come to not only accept but also enjoy change.…”
Section: Child's Impaired Cognitive Functioningmentioning
confidence: 80%
“…Developing a student-centred, learning plan for individuals with FASD (Fetal Alcohol Spectrum Disorder) requires a thoughtful and informed approach in order to create a meaningful, individualized plan that will utilize and develop the strengths of the learner (Carpenter, 2011;Carpenter et al, 2011;Clark, 2012;Clark et al, 2014;Kalberg & Buckley, 2007;Millians, 2015;Pei, 2013;Petrenko, Tahir, Mahoney, & Chin, 2014).…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
“…and Clark et al (2014) completed a mixed-methods study that assessed the POPFASD program. The study was undertaken in one district in British Columbia and participants included 12 elementary teachers from eight schools and 13 students.…”
mentioning
confidence: 99%